Economic Diversification and Growth in Africa Critical Policy Making Issues - Johnson, Omotunde E. G.; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint), 2016)
This book presents a coherent framework for assessing economic policy making in developing countries, with special reference to those in Africa. The chapters focus on policy making issues in three critical areas that are of major importance in the African context: capacity building for domestic resource mobilization; regional integration in Africa and intra-regional trade; and export diversification of individual African countries. Although applying economic theory as well as using case studies and empirical evidence from the economics literature, the book is written in a way that makes the core ideas accessible even to readers without advanced knowledge of the technical economics involved. Economic Diversification and Growth in Africa is a timely study which demonstrates how developing countries in Africa can improve their policy making strategies to diversify their economies and accelerate economic development. Omotunde E. G. Johnson received his PhD in Economics from the University of California, Los Angeles, USA, in 1970. He has taught at universities including the University of Sierra Leone and the University of Michigan, USA, and was International Monetary Fund staff member for more than 25 years. He was Visiting Research Fellow at the Centre for the Study of African Economies and Senior Associate Member at St Antony's College, Oxford University, UK. He has published many articles in academic journals, including the Journal of Law and Economics, Journal of Money Credit and Banking, World Development, Kyklos, Journal of Policy Reform, and International Monetary Fund Staff Papers.
1. Introduction -- 2. Towards Analytic Coherence in Assessing Economic Development Policy Making: Special Reference to African Countries -- 3. Building the Capacity for Domestic Resource Mobilization in African Countries -- 4. Regional Economic Integration in Africa and Intra-Regional Trade -- 5. The Export Challenges for African Countries.
Keywords: Economic Growth; Economic policy; Development economics